The influence of farmland distribution on the performance of the agglomeration bonus - Drechsler, Martin (Frontiers in Environmental Science, 2023)
Coordination incentives like the agglomeration bonus have been proposed to induce the spatial agglomeration of biodiversity conservation efforts and encounter the loss and fragmentation of species habitats. Most theoretical and empirical analyses of the agglomeration bonus make unrealistic assumptions about the spatial structure of landholdings. This paper presents a spatially explicit agent-based simulation model to explore how the spatial structure of landholdings affects the performance of the agglomeration bonus. It turns out that if the number of land parcels per landowner is large and their land is spatially cohesive a higher proportion and agglomeration of conserved land parcels can be achieved for given budget, implying a higher level of cost-effectiveness. This has also implications for the cost-effective design of coordination incentives. The observed effects are especially high if the conservation costs vary strongly in space.